Are dye-sensitized nano-structured solar cells stable? An overview of device testing and component analyses - Egbert Figgemeier; Anders Hagfeldt (International Journal of Photoenergy)
The nano-structured dye-sensitized solar cell (DNSC) is considered as a promising technology having the potential to significantly decrease the costs of solar energy. The breakthrough was achieved in 1991 with the demonstration of a DNSC system reaching more than 7% efficiency and after a decade of intense research the commercialization is in reach. Besides efficiency, stability is equally important for the step from research to the market. Therefore, the stability of such devices has been under close investigation since the DNSC was presented. In this contribution we summarize the literature about device testing and the attempts to understand the degradation mechanisms. Solar cells developed for energy production are discussed as well as alternative systems for low power applications, e.g., DNSCs on plastic substrates. The components (substrate, nano-structured TiO2, dye, electrolyte, additive and counter electrode) are analyzed towards their stability and how it affects the durability of the entire system. From this analysis, guidelines for testing and improving the stability of the DNSC are deduced.